Pack hunting by a common soil amoeba on nematodes. (28th July 2015) - Geisen, Stefan; Rosengarten, Jamila; Koller, Robert; Mulder, Christian; Urich, Tim; Bonkowski, Michael
Summary: Soils host the most complex communities on Earth, including the most diverse and abundant eukaryotes, i.e. heterotrophic protists. Protists are generally considered as bacterivores, but evidence for negative interactions with nematodes both from laboratory and field studies exist. However, direct impacts of protists on nematodes remain unknown. We isolated the soil‐borne testate amoeba C ryptodifflugia operculata and found a highly specialized and effective pack‐hunting strategy to prey on bacterivorous nematodes. Enhanced reproduction in presence of prey nematodes suggests a beneficial predatory life history of these omnivorous soil amoebae. Cryptodifflugia operculata appears to selectively impact the nematode community composition as reductions of nematode numbers were species specific. Furthermore, we investigated 12 soil metatranscriptomes from five distinct locations throughout Europe for 18S ribosomal RNA transcripts of C . operculata . The presence of C . operculata transcripts in all samples, representing up to 4% of the active protist community, indicates a potential ecological importance of nematophagy performed by C . operculata in soil food webs. The unique pack‐hunting strategy on nematodes that was previously unknown from protists, together with molecular evidence that these pack hunters are likely to be abundant and widespread in soils, imply a considerable importance of the hitherto neglected trophic link 'nematophagous protists' in soil food webs.